2021
DOI: 10.1039/d1ra05182b
|View full text |Cite
|
Sign up to set email alerts
|

The ultralow thermal conductivity and tunable thermoelectric properties of surfactant-free SnSe nanocrystals

Abstract: This work demonstrates tunable transport in surfactant free SnSe nanocrystals that retain ultralow nature of thermal conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Figure d shows a comparison of the PF data from this work with reported values for polycrystalline SnS bulks with similar grain size to that of our SnS film and SnSe and SnS thin films deposited by low-cost techniques including spin coating, electrodeposition, thermal evaporation, and pulsed laser deposition. , ,, The PF values for our SnS film deposited at 445 °C by AACVD in the temperature range of 300–520 K are at least comparable to, and in most cases higher than, the PF values reported for SnS bulks with similar grain size with the SnS film. Indeed, up to 520 K, our PF data exceeds that for all SnSe films deposited by other low-cost techniques (Figure d).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Figure d shows a comparison of the PF data from this work with reported values for polycrystalline SnS bulks with similar grain size to that of our SnS film and SnSe and SnS thin films deposited by low-cost techniques including spin coating, electrodeposition, thermal evaporation, and pulsed laser deposition. , ,, The PF values for our SnS film deposited at 445 °C by AACVD in the temperature range of 300–520 K are at least comparable to, and in most cases higher than, the PF values reported for SnS bulks with similar grain size with the SnS film. Indeed, up to 520 K, our PF data exceeds that for all SnSe films deposited by other low-cost techniques (Figure d).…”
Section: Resultssupporting
confidence: 64%
“…Temperature dependence of (a) Seebeck coefficient ( S ), (b) electrical conductivity (σ), and (c) power factor (PF) for SnS films deposited at 397, 418, and 445 °C; (d) Comparison of the PF in this work (red stars) with reported values for SnS bulk materials with similar grain sizes to that of our SnS films and SnSe and SnS thin films (star symbols) prepared by low-cost deposition techniques. , ,, …”
Section: Resultsmentioning
confidence: 91%
“…The thermopower of all the samples was found to be ≈30 μ VK −1 from the slope of Figure S4a–d (Supporting Information), which resulted in a power factor of 51.3 μ WK −2 m −1 , that is about 2.5 times higher than that of polyaniline/graphene nanocomposite [ 50 ] and surfactant‐free SnSe nanocrystals. [ 51 ] In single‐layer graphene, Xiao et al [ 52 ] reported the electrical conductivity in the range of 4 × 10 4 −6 × 10 4 Sm −1 . The low density of structural defects is responsible for the superior electrical conductivity and, correspondingly, lower thermopower of single‐layer graphene.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the quantum size effect, the bandgap energy was larger than that of the indirect bandgap energy of 0.80 eV in bulk SnSe. 40,41) The smaller the QD size, the stronger the quantum confinement effect. The previously reported indirect bandgap energy of 2.27 eV for the 2.5 nm SnSe QDs is slightly smaller than the value of sample F. 42) The bandgap SC1012-4 © 2022 The Japan Society of Applied Physics energies of larger crystals of samples G and H were 1.58 eV and 1.45 eV, respectively, which were smaller than the value of sample F. Since the nanorod of sample H is longer, the bandgap energy was smaller than that of sample G. The bandgap energy of sample D was 1.40 eV.…”
Section: Methodsmentioning
confidence: 99%